2021
DOI: 10.3390/antibiotics10030329
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Pharmacokinetic and Pharmacokinetic-Pharmacodynamic Parameters of Doxycycline against Edwardsiella ictaluri in Yellow Catfish (Pelteobagrus fulvidraco)

Abstract: This study aimed to examine the pharmacokinetics of doxycycline (DC) in yellow catfish (Pelteobagrus fulvidraco) and to calculate related pharmacokinetic–pharmacodynamic (PK/PD) parameters of DC against Edwardsiella ictaluri. The minimum inhibitory concentration of DC against E. ictaluri was determined to be 500 µg/L. As the increase of oral dose from 10 to 40 mg/kg, the area under the concentration vs. time curve from 0 to 96 h (AUC0–96) values were considerably increased in gill, kidney, muscle and skin, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
1
9
1
Order By: Relevance
“…Doxycycline and florfenicol are most commonly used veterinary antibiotics in China (Qian et al, 2021). Previous studies have demonstrated the clinical safety of oral treatment with doxycycline and florfenicol in fish aquaculture (Gaunt et al, 2013;Oliveira et al, 2022), and oral administration of doxycycline and florfenicol are effective in controlling mortality from enteric septicemia of channel catfish Ictalurus punctatus and edwardsiellasis of yellow catfish Pelteobagrus fulvidraco (Gaunt et al, 2013;Xu et al, 2021). In the present study, the DX2 isolate was highly susceptible to doxycycline and florfenicol.…”
Section: Discussionsupporting
confidence: 55%
“…Doxycycline and florfenicol are most commonly used veterinary antibiotics in China (Qian et al, 2021). Previous studies have demonstrated the clinical safety of oral treatment with doxycycline and florfenicol in fish aquaculture (Gaunt et al, 2013;Oliveira et al, 2022), and oral administration of doxycycline and florfenicol are effective in controlling mortality from enteric septicemia of channel catfish Ictalurus punctatus and edwardsiellasis of yellow catfish Pelteobagrus fulvidraco (Gaunt et al, 2013;Xu et al, 2021). In the present study, the DX2 isolate was highly susceptible to doxycycline and florfenicol.…”
Section: Discussionsupporting
confidence: 55%
“…Approved antibiotics for treatment of E. ictaluri infections are Romet ® (a 5:1 mixture of sulfadimethoxine and ormetoprim) and Aquaflor ® (florfenicol) in the USA, enrofloxacin and florfenicol in Vietnam and doxycycline (DC) in China (Table 3). 29,196–199 The constraints of using feed medicated with antibiotics are that the cost of antibiotics can be prohibitive to small‐scale farmers, also, there is emergence of antimicrobial‐resistant strains and the inefficient drug delivery via medicated feed because of loss of appetite in sick fish 29,200–202 . On the contrary, the prevention of E. ictaluri infection can be aided by avoiding stress in fish, use of chemicals, winter overfeeding, production of disease‐resistant hybrids and use of specific pathogen‐free (SPF) fish 40,98,203,204 .…”
Section: Disease Management and Limitationsmentioning
confidence: 99%
“…In studies showing the relationship between the antimicrobial activity of tetracycline and its clinical results through PK and PD indices, it has been determined that the best parameter associated with a successful therapeutic effect is AUC/MIC (De Lucas et al, 2021;Dorey et al, 2017). The PK/PD studies have been performed in various fish and animal species to optimize the therapeutic regimen of DO, but not in rainbow trout (Prats et al, 2005;Xu et al, 2019bXu et al, , 2021Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There are a few studies on the PKs of DO in aquatic animals, including grass crap (Xu et al., 2020b), crayfish (Xu et al., 2022), catfish (Xu et al., 2021) and tilapia (Yang et al., 2014), and other animal species, such as goat. In these studies, it was determined that DO has advantages such as a wide volume of distribution and long elimination half‐life in fish.…”
Section: Introductionmentioning
confidence: 99%